PENGARUH PENERAPAN PRINSIP GOOD GOVERNANCE TERHADAP EFEKTIVITAS KERJA PEGAWAI DISKUMDAG KABUPATEN BARRU - Muhammad Rusdy Yunus; Muhammad Idris; Muhammad Hidayat (Nobel Management Review, 2020)
The purpose of this study was to determine the effect of partially or simultaneously Good Governance factors seen from accountability, transparency, and responsiveness to the work effectiveness of Barru Regency Cooperatives, SMEs and Trade employees. And to find out which factors among accountability, transparency, and responsiveness are the most influential on the work effectiveness of the employees of the Cooperative, SME and Trade Offices of Barru Regency. The method used in this research is quantitative method. The sample in this study were all employees of the Cooperative, UKM and Trade Office of Barru Regency with 36 people. The data analysis technique used in testing the hypothesis is multiple regression analysis with t test and F test. The results of this study indicate that: Good governance factors seen from the aspects of accountability, transparency, and responsiveness partially or simultaneously have positive and significant effect on the work effectiveness of the employees of the Cooperative, SME and Trade Offices of Barru Regency. 5. The most dominant factor of good governance in influencing the increase in work effectiveness of Barru Regency Cooperative, SME and Trade Service employees is the principle of transparency.